ANALISIS PENGARUH PELATIHAN, MOTIVASI KERJA DAN STATUS KARYAWAN TERHADAP KINERJA KARYAWAN PT INDOFARMA (Persero) Tbk - Ichsan Nurdin (Universitas Mercu Buana, 2015)
Abstract. Human resources are an important asset for a company that has theability to evolve as a determinant of success in the long term. Employees who arecompetent and have the ability of high knowledge, motivation and reward in theform of hiring, therefore this thesis discusses the analysis of the effect of training,motivation and employee status on the performance of employees of PTIndofarma (Persero) Tbk. This research approach is quantitative research andresearch is a causal explanatif. The study sample as many as 110 employees of PTIndofarma (Persero) Tbk. The results showed that the training, motivation andemployee status positive influence on employee performance either partially orsimultaneously (parallel) and the highest correlation among the three independentvariables are training. The conclusion of this analysis, training, motivation andhiring should be further improved, because these three discount an important rolein improving the performance of employees.Keywords: employee performance, motivation, training, employee status